Faktor Reinforcing yang Berhubungan dengan Perilaku Remaja Ke Posyandu Remaja Kelurahan Penyengat Rendah Di Wilayah Puskesmas Aurduri Kota Jambi - Ruwayda Ruwayda; M Dody Izhar (Universitas Batanghari Jambi, 2021)
Health education has an important role to change and strengthen behavioral factors, ranging from predisposing, supporting, to driving so that it can lead to positive behavior from the community. But there are still a few who organize youth Posyandu in Jambi City. Aurduri Health Center was the first to form a teen Posyandu. However, teenagers who visited trimester I reached 100 (5%) was 2,005 teeneger. The formation of adolescent Posyandu is expected to be a place to facilitate adolescents in understanding adolescent health problems, find alternative solutions to problems, but there are still adolescents who do not come to adolescent Posyandu so that many adolescents do not know about their health. Design of analytical research with cross sectional design. The object of the study was all teenagers at the public health center Aurduri Jambi city. This study was conducted on February to July 2019. The samples used random sampling as many as 92 respondents. The collecting of data used a questionnaire then analyzed as univariate and bivariate analysis. The findings indicated that (the factors of reinforcing) 71 (77.2%) the role of health personnel is good, 56 (60.9%) the role of teen Posyandu cadres is good, 63 (68.5%) good family support and as many as 75 (81.5%) respondents had good behavior. The results of chi-square test indicated that there is correlation of the role of health personnel, teen Posyandu cadres and family support toward teen behavior to Posyandu p value = 0.000 (p<0.05). It is expected that an increase in the budget, facilities and infrastructure to improve the quality of health services for adolescents, always seek innovation and new breakthroughs so that the interest of adolescents to come to teen POSYANDU increases every month.